Handbook of Japanese music in the modern era (Leiden ; Boston)
xxv, 457 sayfa
Keywords: “Exploring an array of captivating topics, from hybridized Buddhist music to AI singers, this book introduces Japanese music in the modern era. The twenty-five chapters show how cultural change from the late nineteenth century to the present day has had a profound impact on the Japanese musical landscape, including the recontextualization and transformation of traditional genres, and the widespread adoption of Western musical practices ranging from classical music to hip hop. The contributors offer representative case studies within the themes of Foundations, Heritage, Institutions, and Hybridities, examining both musical styles that originated in earlier times and distinctly localized or Japanized musical forms.“ --